Influence of sputtered gallium oxide as buffer or high-resistive layer on performance of Cu(In,Ga)Se2-based solar cells - Witte, Wolfram; Hempel, Wolfram; Paetel, Stefan; Menner, Richard; Hariskos, Dimitrios (Journal of materials research, 2022)
Oxides could be candidates for buffer, passivation, or high-resistive (HR) layers in Cu(In,Ga)Se 2 (CIGS) thin-film solar cells. From an industrial point of view, a high-rate and dry deposition method like sputtering would be the most favorable technique. This study presents results with the wide-bandgap material gallium oxide (Ga 2 O 3 ) deposited by magnetron sputtering applied as a substitution for the traditional CdS buffer or the intrinsic ZnO (i-ZnO) HR layer. With state-of-the-art CIGS absorber layers, subject to a RbF post-deposition treatment, an ammonia rinsing of the CIGS surface before sputtering of X-ray amorphous Ga 2 O 3 has mostly a positive impact on device performance reaching efficiencies up to 14%. An efficiency of 20.2% with anti-reflective coating was achieved with Ga 2 O 3 applied as HR layer as substitution for i-ZnO in combination with a solution-grown CdS buffer and ZnO:Al as front contact. This result is comparable to the efficiency of 20.4% for the CIGS/CdS/i-ZnO/ZnO:Al reference cell. Graphical abstract